Transformational Leadership and Employee Engagement in Hospitality Sector in Sri Lanka (Global Journal of Management and Business Research, 2018)
This study examines the impact of transformational leadership on subordinates#x2019; engagement in the hospitality sector in Sri Lanka. Further, it tests the impact of each dimension (i.e., idealized influence, intellectual stimulation, inspirational motivation, and individual consideration) of transformational leadership on employee engagement. Data were collected through a self-administered questionnaire from 245 executive level employees working in the hospitality sector in Sri Lanka. Findings revealed that transformational leadership and its#x2019; each dimension positively influence the employee engagement in the hospitality industry. Further, the study discusses the practical and theoretical implications.
Keywords: employee engagement; transformational leadership style; the hospitality sector